Enhanced Naturalist Intelligence in Early Childhood through Science Fiction Stories - Murtafiah Murtafiah; Zarina Akbar; Karnadi Karnadi (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
The purpose of this research is to describe the process and the result of the increase of natural intelligence in early childhood B1 RA Asy-Syafi` Kota Tangerang 2018-2019 through research and development science fiction method. The subjects of this study were 12 children. This research method is based on Action Research model of Kemmis and Mc Taggart which includes four stages: planning, action and observation, reflection. This action study was conducted in two cycles and each cycle consisted of 6 meetings. The data collected used in this action research are interviews, observation and documentation. Data analysis technique used in this research is qualitative and quantitative. The result showed that the increased natural intelligence of early childhood RA Asy-Syafi` Kota Tangerang 2018-2019 through science fiction method. The rate of development of focused attention obtained by early childhood in pre cycle is 42,50%. In the first cycle the score is 68,50% and the second cycle is 86,33%. This research reveals that research and development science fiction method is one solution to increase of natural intelligence early childhood.